2008
DOI: 10.1080/14756360802204870
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and preliminary evaluation of new ursolic and oleanolic acids derivatives as antileishmanial agents

Abstract: A series of new ursolic and oleanolic acids derivatives was synthesized via ursolic or oleanolic acids, previously extracted from South American Ilex species. These new compounds were tested for in vitro antiparasitic activity on Leishmania amazonensis and Leishmania infantum strains. Some of these compounds showed activity against the promastigote forms of L. amazonensis or L. infantum, with IC 50 ranging from 5 to 12 mM. As expected, most of the compounds showed a significant level of cytotoxicity against mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 24 publications
(25 reference statements)
1
19
0
2
Order By: Relevance
“…Studies conducted by Tan et al (2002) demonstrated that oleanolic and ursolic acids from Salvia cilica were more efficient in the elimination of intracellular forms of Leishmania donovani and Leishmania major than promastigotes, indicating that amastigotes present elevated sensibility to these compounds. In addition, other studies have demonstrated the potential of synthesized oleanolic and ursolic acids in the elimination of L (L.) amazonensis and L. donovani parasites (Gnoatto et al 2008), indicating the possibility of large-scale production of both compounds; moreover, the strong inhibitory activity against different species of Leishmania reinforcing the possibility of drug development. Besides oleanolic+ursolic acids and pectolinaringenin, caffeic acid also presented moderate activity against amastigote forms of L. (L.) amazonensis, but weak against L. (V.) braziliensis amastigotes, and low cytotoxicity has been verified on J774 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Tan et al (2002) demonstrated that oleanolic and ursolic acids from Salvia cilica were more efficient in the elimination of intracellular forms of Leishmania donovani and Leishmania major than promastigotes, indicating that amastigotes present elevated sensibility to these compounds. In addition, other studies have demonstrated the potential of synthesized oleanolic and ursolic acids in the elimination of L (L.) amazonensis and L. donovani parasites (Gnoatto et al 2008), indicating the possibility of large-scale production of both compounds; moreover, the strong inhibitory activity against different species of Leishmania reinforcing the possibility of drug development. Besides oleanolic+ursolic acids and pectolinaringenin, caffeic acid also presented moderate activity against amastigote forms of L. (L.) amazonensis, but weak against L. (V.) braziliensis amastigotes, and low cytotoxicity has been verified on J774 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Antileishmanial activity of ursolic acid was also evaluated against promastigotes of Leishmania amazonensis (IC 50 = 43.8 and 5 g/ml, depending on the test) (Torres-Santos et al, Gnoatto et al, 2008) and against promastigotes of Leishmania donovani (IC 50 = 3.5 g/ml) (Moulisha et al, 2010). The activity of oleanolic acid against promastigotes of Leishmania amazonensis gave an IC 50 of 10 g/ml (Torres-Santos et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies it was shown that ursolic acid (2) had moderate activity against L. amazonensis but was inactive against L. infantum (Gnoatto et al, 2008). Also, Torres-Santos et al showed that ursolic acid isolated from Pourouma guianensis Aublet (Moraceae) had a mild in vitro activity (IC 50 ¼59 mM) against intracellular amastigotes of Leishmania amazonensis (Torres-Santos et al, 2004).…”
Section: ) Wert Et Al Showed a Series Of Synthetic Betulin Derimentioning
confidence: 95%